Understanding the relationship between pet owners and their companion animals as a key context for antimicrobial resistance-related behaviours: an interpretative phenomenological analysis. Issue 1 (1st January 2019) - Dickson, A.; Smith, M.; Smith, F.; Park, J.; King, C.; Currie, K.; Langdridge, D.; Davis, M.; Flowers, P.
ABSTRACT: Objectives: Drivers of antimicrobial resistance (AMR) are diffuse and complex including a range of interspecies behaviours between pet owners and their animals. We employed interpretative phenomenological analysis (IPA) to explore the relationship between pet owners and their companion animals in relation to AMR. Design: Cross sectional, qualitative study. Methods: Semi-structured interviews were conducted with twenty-three British pet owners, transcribed verbatim and subjected to Interpretative Phenomenological Analysis (IPA). Results: Three, inter-related Superordinate themes are presented 1) 'They're my fur babies': unconditional love and anthropomorphism; 2) 'They share everything with you': affection and transmission behaviours; and 3) 'We would err on the side of caution': decision making and antibiotic use'. Conclusions: Affectionate behaviours between companion animals and their owners pose a risk for AMR transmission but they are so deeply treasured that they are unlikely to be amenable to change. In contrast, the promotion of appropriate antibiotic stewardship for pet owners and vets may offer a viable pathway for intervention development, benefitting from synergies with other interventions that target prescribers.